Improving dietary diversity among women of reproductive age group (15-49 years) through community-based activities across four districts of India - Rastogi, Priyanshu; Choudhary, Santosh; Mehra, Sunil; Sharma, Shantanu (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally, more than two billion people have micronutrient deficiencies (MiNDs), with approximately half of them residing in India. Nutri-gardens offer the opportunity to diversify a family's diet. The objective of the present study is to assess the effectiveness of growing nutri-gardens in improving the dietary diversity of women and girls compared to no nutri-gardens. Methods: It was a post-test-only comparison with a control group. The intervention and control groups were similar in all aspects except that the intervention group received seeds for growing a nutri-garden. A random sample of 100 adolescent girls (15-19 years) and women per district in the intervention and control groups was drawn from four districts. A campaign was launched to spread awareness of nutri-gardens, a balanced diet, and food groups. The data were collected using a pre-designed semi-structured questionnaire that included a standardized diet quality questionnaire. Results: In total, there were 804 women and adolescent girls. Out of 804, 457 grew (the intervention group) and 347 did not grow nutri-garden (the control group). Women and girls who grew nutri-gardens had 0.38 times higher odds of having higher dietary diversity (≥5) than women and girls who did not. Similarly, women and girls who are educated have higher odds of having a higher dietary diversity compared to illiterates. Conclusions: The study concludes that establishing nutri-garden along with nutrition education improved dietary diversity among girls and women in the intervention areas. Nutri-garden is a low-cost sustainable approach to providing fruits and vegetables daily and meeting their daily requirements.